Retrenchment Law in Indonesia and Malaysia: A Comparative Evaluation - SANTOSO, Budi; HASSAN, Kamal Halili; DHEVIANA PH, Ratih (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The purpose of this article is to make a comparative evaluation on retrenchment law in Indonesia and Malaysia. It is focused on the justified circumstances, the procedure and the worker’s entitlements. By using a comparative approach and such methods as synthesis and analysis, the evaluation conclude that the Indonesian labor law does not prescribe specific provisions on the retrenchment, neither definition nor justified circumstances. Similarly, the retrenchment is not defined under the Malaysian labor law as well. However, the Malaysian law provides circumstances that justify the retrenchment and recognizes it as an employer’s prerogative. On the issue of the procedure to be adopted in an impending retrenchment, Malaysia provides it under the Code of Conduct for Industrial Harmony. Although it is not a mandatory, application of the procedure can be enforced by the Industrial Court. In Indonesia, despite there are no specific rules on the procedure, the law indeed has procedural requirements for any termination of employment. In the matter of the worker’s entitlements, both countries have a legal provision governing the retrenched worker entitled to retrenchment payments, but have no specific legal provision on the priority of re-employment. Nevertheless, this priority is provided by the Code in Malaysia.